Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-04-11T19:45:02+02:00
A) (4-2x)-(x+3) =(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
1-3x=-8
-3x=-9
x=3

b)(3-2x)+(3x+4)=-(3- 2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
7+x=2x+6
-x=-1
x=1

c)-(x+3)+(2x-1)=(1+4x) +(3+x)
-x-3+2x-1=1+4x+3+x
x-4=4+5x
-4x=8
x=-2

d)-(x+3)- (2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x-11=-2
-3x=9
x=-3

e) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x+6=5
-x=-1
x=1

f) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x-2=-4
-x=-2
x=2

g)2 (x+4) -5(x+3)=2
2x+8-5x-15=2
-3x-7=2
-3x=9
x=-3

h) -2(x+3)+4(2x +3)= -6
-2x-6+8x+12=-6
6x+6=-6
6x=-12
x=-2
2010-04-11T19:46:47+02:00
A) (4-2x)-(x+3) =(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3-4+3
-3x=-9 |*(-3)
x=3

b)(3-2x)+(3x+4)=-(3- 2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6 |:(-6)
x=1

c)-(x+3)+(2x-1)=(1+4x) +(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+3+1
-4x=8 |:(-4)
x=-2

d)-(x+3)- (2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+3+8
-3x=9 |:(-3)
x=-3

e) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x=5+6-12
-x=-1 |*(-1)
x=1

f) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
3x-4x=-4+12-10
-x=-2 |*(-1)
x=2

g)2 (x+4) -5(x+3)=2
2x+8-5x-15=2
2x-5x=2-8+15
-3x=9 |:(-3)
x=-3

h) -2(x+3)+4(2x +3)= -6
-2x-6+8x+12=-6
-2x+8x=-6+6-12
6x=-12 |:6
x=-2